Complete genome sequence of Desulfobulbus propionicus type strain (1pr3(T)) - Pagani, Ioanna (Michigan State University, 2011)
Desulfobulbus propionicus Widdel 1981 is the type species of the genus Desulfobulbus, which belongs to the family Desulfobulbaceae. The species is of interest because of its great implication in the sulfur cycle in aquatic sediments, its large substrate spectrum and a broad versatility in using various fermentation pathways. The species was the first example of a pure culture known to disproportionate elemental sulfur to sulfate and sulfide. This is the first completed genome sequence of a member of the genus Desulfobulbus and the third published genome sequence from a member of the family Desulfobulbaceae. The 3,851,869 bp long genome with its 3,351 protein-coding and 57 RNA genes is a part of the Genomic Encyclopedia of Bacteria and Archaea project.